DEROGATORIA DEL SILENCIO ADMINISTRATIVO EN APLICACIÓN A LOS DERECHOS DE LIBERTAD QUE TODA PETICIÓN DEBE SER CONTESTADA CON RESPUESTAS MOTIVADAS Y CUMPLIENDO LOS PLAZOS FIJADOS EN LA LEY - Jiménez Criollo, Ligia del Cisne (2016)
The transcendence of the object of study in this research is a problem of public law that it is called Administrative Silence repeal in application to the rights of freedom that any petition must be answered with motivated answers and fulfilling the period concentrated on the law, it is sustained in the need to clarify the provisions of the Constitution of the Republic of the Equator about the right of petition and the obligation to give him a based response and the procedure of the Law of Modernization of the State that regulates the Administrative Silence. In this thesis we have demonstrated that the Administrative Silence can not exist against the imperative order of impugnation of the planned acts in the Constitution of the Republic of the Equator in the Article 173 before the administration and before the juridical function and for the right of petition that would force the administration to give answer to any request presented for the administered. In addition, the Administrative Silence is not in the competence of the administrators, they are obliged to fulfill their responsibility. And it is not expressly repealed the Administrative Silence, in shape undue the administration comes it using. There the importance of this work whose hypothesis was raised as well: “The Administrative Silence foreseen in the Law of Modernization of the State contradict the rule 23 of the Article 66 of the Constitution of the Republic of the Equator so the derogation is required for realizing rights managed”, the same one that has been justified with this study that we submitted for consideration of the general public. Likewise it has allowed to present the juridical proposal to solve this problem.